Analysis of Solar Collector Adsorption Cooling Machine Using 3D Simulation - John Peter Simanjuntak (International Journal of Mechanical Computational and Manufacturing Research, 2021)
Solar Energy is the biggest energy on the earth, solar enegy in Indonesia can be utilized for variety of things. Based on solar radiation data collected from 18 locations in Indonesia, solar radiation for West Indonesia area has reached 4,5 kWh/m2/day with monthly variation about 10%, while East Indonesia area has reached about 5,1 kWh/m2/day with monthly variation about 9%. Therefore, the solar energy can be utilized as the main source of energy for the adsorption refrigeration cycle cooling machine to produce cooling effect. The simulation object of this research is collector, which simulated with Fluent Ansys 15.0 software and modeled with 3D CAD software. The surface area of this collector is about 1m2,covered with 2 glass covers and tilted at 0o The result from this simulation is the theoretical solar energy that adsorbed into collector about 10,472 MJ, average temperature at upper collector plate about 92,5℃, average temperature at lower collector plate about 89,95 ℃, and average temperature at upper glass cover about 82,92℃.